John Calvin and Creation : Retrieving Ecological Insights of Calvin on Genesis 1 - Kavusa, Kivatsi Johnathan (Stellenbosch Theological Journal, 2022)
John Calvin has been largely studied given his influential role in the Reformation. I come from a Church with strong Calvin traditions. During catechisms, we were mainly taught about Calvin's theology in areas such as predestination, redemption, Christology, power and sacramental theology. Little has been said regarding the ecological dimensions of his thoughts. It is only recently that the Presbyterian Church has issued the devotional study guide in response to the United Nations Sustainable Development Goals (2015). But the manual is more report than a systematic ecological teaching based on Calvin. The question is how far Calvin's cosmology can contribute to shape Christian attitudes toward nature. This article tries to answer this question by retrieving the ecological implications of Calvin's comments on different aspects of Genesis 1.